Improving livelihoods in East Africa through livestock research and extension: reflections on changes from the 1950s to the early twenty first century - Omore, Amos O.; Kurwijila, Lusato R.; Grace, Delia (Springer, 2009)
This paper discusses the major changes in development thinking that, in our view, have characterized livestock research and extension in Africa since the 1950s. It describes the institutional and ideological environment in which research and extension was then conducted and provides examples of early successes aimed at enhancing productivity. There was then a gradual broadening of the scope of research and extension to internalize the wider contexts of the challenges of improving livelihoods. The four main over-arching changes discussed are: poverty-focus, gender-sensitivity, participation and holism. The discussion ends by speculating on directions for the future.